Retalho miocutâneo infrahioideo em cirurgia reconstrutora de cabeça e pescoço: análise retrospectiva dos resultados precoces em 38 casos - Gustavo Meyer de Moraes (2011)
Introduction: Use of axial flaps is the preferred method for surgical reconstruction following substance loss. In head and neck surgeries, they are routinely used for covering defects due to surgical removal of tumors. Despite the advent of microsurgical flaps, axial flaps are still very much used since they are simpler and demand less surgical time than that spent in microsurgical surgical reconstructions. The infrahyoid myocutaneous flap (IMF) was first described in 1986; however, this reconstruction method is not well known in our midst. Objective: Evaluate, retrospectively, the initial results of IMF use regarding applicability and complications. Method: We studied 38 cases, operated on by three different surgeons. Of these, one had previous experience with the technique, while the other two were introduced to this reconstruction methodology during this study. The reconstructed areas were evaluated and confronted with the incidence of complications, age of patient, tumor stage, and surgeon responsible for the case. Results: IMF was used for surgical reconstruction in various subareas of the head and neck. In 29 of the cases (76,36%), the flap was used for reconstruction of the inferior mouth. Surgeon performance was similar between the three surgeons in regard to complications. When investigating the possible association between the degree of lymph node involvement and the occurrence of complications, no significant association was found. The results appoint to significant association between the stage of the primary tumor and dehiscence of the flap donator area (p=0,0029). All other complications of IMF had no significant association to the stage of the primary tumor. There was no significant relation between the age of patients and the occurrence of complications. Conclusions: Infrahyoid myocutanous flap can be applied to the reconstruction of various subareas, its main use being in the inferior half of the mouth. The results presented in literature can be reproduced and complication rates are not related to a patients age or lymph node involvement. Dehiscence incidence was significantly higher in patients with T4 stage tumors.